1993
DOI: 10.1111/j.1471-4159.1993.tb07455.x
|View full text |Cite
|
Sign up to set email alerts
|

Soluble and Particulate Organophosphorus Neuropathy Target Esterase in Brain and Sciatic Nerve of the Hen, Cat, Rat, and Chick

Abstract: Considerable evidence exists suggesting that the so-called neuropathy target esterase (NTE) is involved in the mechanisms responsible for organophosphorus-induced delayed polyneuropathy (OPIDP). Earlier studies in the adult hen, the habitually employed experimental model in OPIDP, have shown that most NTE activity in the brain is centered in particulate fractions, whereas approximately 50% of this activity in the sciatic nerve is encountered in soluble form, with the rest being particulate NTE. In the present … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
6
2
1

Year Published

1994
1994
2010
2010

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(11 citation statements)
references
References 9 publications
(8 reference statements)
2
6
2
1
Order By: Relevance
“…The concentration of NTE activity observed in the bovine adrenal medulla (5000 mU/g tissue) was higher than the concentrations described for any other nervous tissues of avian, mammalian, or acuatic species in which studies had been performed (22); specifically, NTE activity was found to be 2-2.5 times that reported in hen brain (5,(21)(22)(23)(24), the most abundant enzyme source. However, specific NTE activity in the adrenal medulla (75 mU/mg protein) was similar to that described by Reiner et al (25) in hen brain (60.3 mU/mg protein) and higher to that reported by Correl and Enhrich from chicken, turkey, quail, and rat brain (26) and by the same authors for hen brain (27).…”
Section: Discussioncontrasting
confidence: 64%
See 1 more Smart Citation
“…The concentration of NTE activity observed in the bovine adrenal medulla (5000 mU/g tissue) was higher than the concentrations described for any other nervous tissues of avian, mammalian, or acuatic species in which studies had been performed (22); specifically, NTE activity was found to be 2-2.5 times that reported in hen brain (5,(21)(22)(23)(24), the most abundant enzyme source. However, specific NTE activity in the adrenal medulla (75 mU/mg protein) was similar to that described by Reiner et al (25) in hen brain (60.3 mU/mg protein) and higher to that reported by Correl and Enhrich from chicken, turkey, quail, and rat brain (26) and by the same authors for hen brain (27).…”
Section: Discussioncontrasting
confidence: 64%
“…that reported by other authors in hen brain (5,(21)(22)(23)(24), and specific activity (25 mU/mg protein) was considerably lower than that observed by Reiner et al (25) from hen brain: however, it was similar to that described from chicken and turkey brain and somewhat higher than quail and rat brain (26).…”
Section: Discussioncontrasting
confidence: 54%
“…The function of NTE-R1 is unknown, although it may be related to esterase activities in different fractions of hen brain and sciatic nerves [30][31][32] . Our results clearly show that Nte-R1 cannot substitute for Nte during embryonic development and that it is not responsible for the effects of EOPF.…”
Section: Discussionmentioning
confidence: 99%
“…At predetermined time points (usually 24 and 48 h following dosing), subsets of hens (3 per time point) are killed and the brain and lumbar spinal cord are removed and prepared for the in vitro determination of NTE (Johnson, 1977(Johnson, , 1982Kayyali et al, 1991;Soliman et al, 1982;Sprague et al, 1981;Zech and Chemnitius, 1987). Sciatic nerve tissue may also be assayed for NTE (Carrera et al, 1994;Moretto et al, 1991;Tormo et al, 1993). The test method is a differential assay of the ability of neural tissue, following OP exposure, to hydrolyze a phenyl valerate substrate selectively.…”
Section: Delayed Neurotoxicity Of Organophosphorus Compoundsmentioning
confidence: 99%